2015
DOI: 10.1016/j.proeng.2015.11.111
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pavement Condition on Vehicle Speeds and Motor Vehicles Emissions

Abstract: Pavement deterioration that happens at the highways causing huge losses, particularly for road users, such as increased journey time, congestions, accidents and etc. Moreover, the oncoming vehicles at slow speed will create more pollution through greater emissions and its impression on human wellness. This research examines how road damages effects of the vehicle speed subsequently to the motor vehicle emission. This research stages begins with assessment of pavement condition uses PCI methods, six locations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…With regard to hourly traffic conditions, the sign of the parameters is supported by traffic operations principles in which free-flow conditions are associated with off-peak traffic hours when drivers can assume higher speed levels ( 39 ). As for road conditions, two different studies by Edwards ( 40 ) and Setyawan et al ( 41 ) showed that lower speeds were typical of wet pavement surfaces and poor pavements. For vehicle type, heavier vehicles showed a decrease in SA, which is in agreement with the findings of the study done by Wang et al ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to hourly traffic conditions, the sign of the parameters is supported by traffic operations principles in which free-flow conditions are associated with off-peak traffic hours when drivers can assume higher speed levels ( 39 ). As for road conditions, two different studies by Edwards ( 40 ) and Setyawan et al ( 41 ) showed that lower speeds were typical of wet pavement surfaces and poor pavements. For vehicle type, heavier vehicles showed a decrease in SA, which is in agreement with the findings of the study done by Wang et al ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…The equations proposed by Setyawan and Kusdiantoro [57] and Duarte et al [58] for CO, NO, MP, and CO2 emissions were adapted. Table A.…”
Section: A31 Environmental Costsmentioning
confidence: 99%
“…This approach has been used in [10] to estimate GHG, NO x , CO and SO 2 in Mauritius where traffic counts (i.e., AADT) for all road classes are split by fuel type and fuel consumption is calculated by vehicle type and road class. Similarly, [51] estimate NO, CO 2 , SO, PM and CO for a particular road in Indonesia and [52] calculated VKT from traffic counts to estimate CO, NO x , PM 2.5 and volatile organic compounds (VOC) emitted from trucks on major roads in a Korean metropolitan area. [53] also utilised traffic counts to calculate VKT and emissions factors for each fuel and vehicle type to estimate CO 2 in Dhaka, Bangladesh and [54] estimated road transport emissions from VKT based on AADT, to distribute emissions along the road network in Salt Lake City, Utah.…”
Section: Literature Reviewmentioning
confidence: 99%